Evaluating a novel team learning approach for integrating drugs in sports education in preclinical medical training - Pelobello, Samuel; Potter, Grayson; Rogstad, Daniel K.; Mock, Andrew J.; Wilson, Sean M. (Frontiers in Medicine, 2025)
Use of performance-enhancing drugs and supplements continues to be pervasive in sports. Medical practitioners are key because they are well positioned to prevent doping among athletes as they are a trusted resource for the patients whom they serve. At Loma Linda University School of Medicine, we are seeking to provide medical students with education on the topic of drugs in sports so that they can better serve their patients. This study evaluated the implementation of a novel Case-Based Team Learning session on drugs in sports for preclinical first year (MS1) and second year (MS2) medical students. The session aimed to introduce fundamental concepts of performance-enhancing drugs, anti-doping regulations, and patient communication strategies within the context of sports medicine. Post instructional survey data on the learning environment and qualitative feedback responses were collected from 189 MS1 and 170 MS2 students. Results of the quantitative data showed that MS1 students rated the session more positively than MS2 students. Qualitative data was collected through open-ended questions, allowing for more detailed and nuanced responses. AI models were used to identify common themes and patterns in the qualitative feedback responses. These responses provided valuable insights for future curriculum refinement and development of the newly implemented drugs in sports education program. Both cohorts appreciated the interactive nature of the session and real-life applications but identified areas for improvement, including better alignment with curriculum objectives and exam preparation. Key challenges included balancing content relevance with broader medical education goals and integrating communication skills training within a large group setting. Faculty reflection highlighted the need for restructuring the session to better match instructional block content and USMLE Step 1 exam preparation. Future iterations will focus on emphasizing drug pharmacology, mechanisms of action, and physiological effects for MS1 students, while providing opportunities for more comprehensive knowledge integration through the case studies for MS2 students. This evaluation of the learning session underscores the importance of iterative curriculum development in medical education, particularly when introducing novel topics like drugs in sports.